2013
DOI: 10.1021/cg3016172
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Cubic and Hexagonal InN Thin Films via Plasma-Assisted Atomic Layer Epitaxy

Abstract: InN thin films possessing either a novel cubic or a hexagonal phase were grown by plasma-assisted atomic layer epitaxy on an a-plane sapphire, Si(111), and GaN/sapphire templates, simultaneously. Two ALE growth temperature windows were found between 175–185 °C and 220–260 °C, in which the growth process is self-limiting. In the lower temperature ALE window, InN on an a-plane sapphire crystallized in a face-centered cubic lattice with a NaCl type structure, which has never been previously reported. InN grown on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 26 publications
5
69
0
Order By: Relevance
“…• C. 25 Additionally, they reported that N rich InN films were insulating while In rich InN films exhibited lower resistivity. Less resistive In rich films were correlated with nitrogen vacancies (V N ) which is the major contributing source of electrons in InN films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C. 25 Additionally, they reported that N rich InN films were insulating while In rich InN films exhibited lower resistivity. Less resistive In rich films were correlated with nitrogen vacancies (V N ) which is the major contributing source of electrons in InN films.…”
Section: Resultsmentioning
confidence: 99%
“…23, 24 Nepal et al have reported atomic layer epitaxy (ALE) of InN thin films on sapphire, the conventional substrate material for III-nitride growth, utilizing quartz-based inductively coupled plasma source. 25 On the other hand, silicon, the material of choice for micro-electronics industry, offers cost-effective, large wafer-diameter, high-quality substrates with inherent CMOS manufacturing compatibility. Highquality III-nitride layers grown on Si at low temperatures (<400…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of InN deposition by atomic layer deposition (ALD) have shown that it is indeed possible to deposit InN with high crystalline quality using In(CH3)3 and nitrogen plasmas. 6,7 For use in electronics, one of the most important aspects of the deposited InN film is low impurity levels, particularly for carbon and oxygen. It is a well-known problem in ALD that the low deposition temperatures used to maintain self-limiting behaviour can lead to carbon impurities in the few atomic percent range when metal precursors with metal-carbon bonds are used.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nepal et al [11] deposited InN thin films having either a novel cubic and/or a hexagonal structure by PA-ALE using InMe 3 and N 2 plasma. In the present study, the film deposited using N 2 plasma only has shown to possess superior properties compared to those deposited using a mixture of N 2 and H 2 plasma.…”
Section: (Opto)electronic Device Applications Of Gan Thin Filmsmentioning
confidence: 99%
“…Although thermal ALD (or atomic layer epitaxy, ALE) of III-nitride thin films, especially AlN, using various types of group-III precursors has been the focus of interest in the 1990s, current trend in the field of III-nitride ALD research is directed towards UV-, hot-wire-or plasmaassisted processes using metalorganic precursors [1][2][3][4][5][6][7][8][9][10][11]. Recently, we showed that ALD-grown III-nitride thin films may suffer from plasma-related oxygen contamination depending on the choice of N-containing plasma gas (N 2 , N 2 /H 2 or NH 3 ) [12,13].…”
mentioning
confidence: 99%